2018
DOI: 10.21595/chs.2018.20430
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between acute atrial fibrillation and local earth magnetic field strength

Abstract: Objectives: Atrial fibrillation is the most frequent cardiac arrhythmia affecting over 3 percent and appears to be increasing in general population. In addition to widely discussed such risk factor as obesity, arterial hypertension, electrolytes disbalances and dysfunction of thyroid, there is more and more evidence of human heath interactions with environment parameters such as humidity, temperature, the lunar and the solar activity. Atrial fibrillation, a disorder of heart conductive system, in several studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This is the rst study we are aware of that focused on the correlations between cardiovascular function and changes in LMF strength in different frequency ranges and at different fractal levels. Moreover, there are only a few publications on changes in the local MF impact on human health [25,[23][24][25][26][27][28][29], while many publications analyse the impact of the disturbances in the Global MF on living organisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is the rst study we are aware of that focused on the correlations between cardiovascular function and changes in LMF strength in different frequency ranges and at different fractal levels. Moreover, there are only a few publications on changes in the local MF impact on human health [25,[23][24][25][26][27][28][29], while many publications analyse the impact of the disturbances in the Global MF on living organisms.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that not only enhancement but also weakening of the resonant frequencies in the magnetic eld can adversely affect the body and that the direction of the LMF intensity change has an impact [21]. Clearly, increased LMF activity in low frequency ranges has a positive effect on the course of ischemic heart disease (IHD) [21,[23][24][25][26][27][28][29] but may increase risk of acute arrhythmias [25]. This study has con rmed that higher LMF intensity in the high frequency ranges is associated with higher number of admissions due to ACS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects are much more pronounced in patients with CVD and other risk factors [7,9]. A stronger association between arrhythmias, such as acute atrial fibrillation, and fluctuations in local magnetic field activity has been found in groups of individuals with arterial hypertension [4]. Studies show that the intensity of the magnetic field at different frequencies affects the body differently: in the low frequency range it has a positive effect on human health, while in the higher frequency range it is associated with increases in health disorders [2][3][4].…”
Section: Introductionmentioning
confidence: 99%